Comparison study of metformin versus insulin in the treatment of gestational diabetes during pregnancy - Nanda, Pratibha; Kabra, Shashi L.; Madaan, Richa; Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Gestational diabetes was traditionally treated with insulin. Metformin is a peroral drug used worldwide in the treatment of type 2 diabetes and also in a few studies on patients with gestational diabetes. This study aimed to analyze and compare insulin and metformin in the treatment of gestational diabetes and to compare their effects on the pregnancy outcomes. Method: This comparative prospective observational study was conducted at Deen Dayal Upadhyay Hospital, New Delhi, a tertiary care teaching hospital. The data was collected over a period of 15 months (April 2021 till June 2022). So pregnant females in the age group 18-45 years with 20-30 weeks period of gestation, are diagnosed with gestational diabetes as per the diabetes in pregnancy India (DIPSI). The study group was divided into 2 groups of 40 each, one receiving oral metformin and the other group receiving insulin for treatment. Results: Metformin was found to be a better drug in controlling blood sugars vis a vis insulin in our study. GDM patients controlled on insulin were found to be associated with; higher weight gain, higher incidence of neonatal hypoglycemia, hyperinsulinemia and higher and longer ICU admission Conclusions: Metformin was better in controlling blood sugar in GDM than insulin, with better neonatal outcome.